Voltammetric study of the interaction of Cu(II) with proton pump inhibitor at different pH - Biswas, R; Das, MC; Islam, S; Haque, MA; Shaikh, AA (Bangladesh Journal of Scientific and Industrial Research, 2015)
The electrochemical redox behavior of transition metal ion, Cu(II) at different pH in acetate buffer solution has been investigated using cyclic voltammetric method at glassy carbon electrode (GCE). Cyclic voltammograms of Cu(II) show two cathodic and an anodic peaks those remain identical at various pH. The cyclic voltammetric response of the metal ion has been observed in presence of proton pump inhibitors (PPIs) such as omeprazole, pantoprazole, esomeprazole and rabeprazole at various proportions of metal ion and PPIs. The nature of cyclic voltammograms of Cu(II) has been changed dramatically in presence of the PPIs due to the strong interaction between metal ion and PPIs. Almost similar interaction was noticed for all the PPIs. However, the maximum interaction was found at 1:2 molar ratio of Cu(II) and PPIs. The result could provide deep insight into the interaction between various metal ions and the PPIs that have been taken quite regularly in human body Bangladesh J. Sci. Ind. Res. 50(3), 219-226, 2015